Beyond Big Gold Mountain: Chinese-Australian Settlement and Industry as Integral to Colonial Australia. Issue 2 (4th May 2019) - Beynon, David
ABSTRACT: Australian historiography has generally treated both the architecture and the industry of non-Western immigrants as marginal phenomena. However, Chinese settlements were not only integral to the nineteenth-century goldmining industry in Australia, but also critical to the wider development of northern Australia. Beyond this, Chinese settlers were instrumental in the establishment of market gardening, plantation agriculture, cabinet making, and laundry industries in the late nineteenth century, all of which had architectural manifestations that provided integral if unprivileged elements to Australia's developing cultural and aesthetic landscape. The following text aims to provoke ongoing questions about Australia's architectural identity in a context where reconsideration of the integral role of Chinese settlers in the development of Australian society might not only apply more widely to the flows of people from China in the period of Australia's establishment as a nation but also to the contributions of Chinese-Australian industry to the local built environment.